Comparison of two surgical approaches for Laparoscopic Ovum Pick Up in Ewes - Mariano, R. S. G. [UNESP] (2019)
The present study had as an aim to evaluate a right lateral access as an alternative method to laparoscopic ovum pick-up (LOPU) in sheep. Twenty-four Santa Ines ewes were randomly assigned in two groups with twelve animals each: RLD - positioned in right lateral decubitus, with 10 degrees head-down tilt; and DD - positioned in dorsal decubitus with 35 degrees head-down tilt. The following parameters were evaluated every 10 minutes during the procedure: total surgical time (ST), visualized follicles (VF), aspirated follicles (AF), recovered oocytes (RO), mean arterial pressure (MAP), heart rate (HR), respiratory rate (fR) and end tidal CO2 pressure (EtCO2). Pre and postoperative arterial hemogasometry parameters (PaO2, PaCO2, pH, CHCO3 and BE) were also evaluated; and serum fibrinogen levels (SFL) on postoperative period. The values of VF, AF, RO, fR, PaO2, pH, CHCO3, BE and SFL were similar between groups, although ST, HR, MAP, EtCO2 and PaCO2 were higher in LG. Regarding operative periods, PaO2 and pH were lower after surgery (PaO2: 79.1 +/- 16.4; 79.2 +/- 11.7mmHg; pH: 7.30 +/- 0.09; 7.32 +/- 0.08) in both groups when compared to preoperative (PaO2: 80.1 +/- 14.3; 83.4 +/- 10.5 mmHg; pH: 7.38 +/- 0.05; 7.39 +/- 0.05) while PaCO2 (43.6 +/- 4.6; 41.9 +/- 5.4mmHg) and CHCO3 (22.8 +/- 1.5; 22.7 +/- 3.0mmol/L) increased (PaCO2: 54.3 +/- 10.9; 46.9 +/- 6.3mmHg; CHCO3: 24.8 +/- 3.4; 24.4 +/- 2.7mmol/L) postoperative. This alternative decubitus presented is a viable procedure and did not differ in oocyte recovery rates in ewes. However, entails cardiorespiratory major alterations compared to conventional procedure, making its practical applicability limited.